Desenvolvimento de um protótipo de aplicações interativas para TV Digital no Middleware Ginga com objetos NCL - Antunes, Marco Aurelio Migliorini [UNESP] (2015)
The Digital Interactive TV (DTV) presents interactivity as a facilitator in the process of interaction where, through it, direct communication with their viewer is possible. Thus, this paper seeks to show the essential foundations and features of the iDTV as local interactivity instrument, analyze its implementation in Brazil and study the forms of interactivity. For this, we intend to demonstrate the development of a prototype application for iDTV middleware Ginga in place with interactivity and NCL objects, which seeks to insert interactivity in a television commercial, with the goal of providing a support tool and additional information to the viewer. It is believed that interaction with iDTV can bring many innovations to the advertising area in the coming years, improving the contact between companies and customers, and may even become a trend in viewing and testing of products. The development of this prototype aims to study the development of the local interactive models easy to use and understand data, providing new possibilities for TV products. To this end, it took some changes while creating the project so that use was facilitated by user as well as the provision of information on the screen to ofter the least harm to the original commercial, as it aims to add information to the viewer